The role of English as a foreign language learners’ grit and foreign language anxiety in their willingness to communicate: Theoretical perspectives - Wang, Minqi; Wang, Hui; Shi, Yan (Frontiers in Psychology, 2022)
Learners’ willingness to communicate in a foreign language is regarded as a critical issue in educational contexts, so the role of emotional factors in learners’ willingness to communicate has drawn the attention of investigators. This review investigated the studies on the relationship between English as Foreign Language (EFL) learners’ grit, foreign language anxiety, and willingness to communicate. This review showed a significant relationship between learners’ grit and willingness to communicate. The earlier studies showed that gritty learners with incessant inspiring efforts are more likely to communicate in a foreign language. This review also indicated that lower anxious learners tend to have more willingness to communicate. Moreover, the study has some pedagogical implications and suggestions for teachers, learners, syllabus designers, material developers, teacher educators, policy-makers, and advisors. The ideas can improve their awareness of teachers’ willingness to communicate, grit, and foreign language anxiety in educational environments.